Rare Ameloblastic Carcinoma Metastasis to the Cervical Spine: A Case Report. Issue 6 (20th June 2021) - Salehani, Arsalaan; Mooney, James; Lepard, Jacob; Hackney, James R; Harmon, Daniel
Abstract: BACKGROUND AND IMPORTANCE: Ameloblastic carcinoma (AC) is a malignant neoplasm of epithelial origin that typically arises from the mandible or maxilla. It represents approximately 2% of all odontogenic tumors. Gross total resection is the surgical goal given AC's aggressiveness and propensity for recurrence. We present the first reported AC metastasis to the cervical spine. CLINICAL PRESENTATION: A 61-yr-old African American female with a history of AC of bilateral mandibles and lung metastases presented with neck pain and right arm weakness progressive over several months. Cervical spine imaging demonstrated a cervical 3 pathological fracture with severe anterior vertebral body compression and resultant cervical 2-3 kyphotic deformity and bony retropulsion causing severe cord compression. The patient underwent a cervical 3 corpectomy and cervical 2-4 anterior fixation followed by a cervical 3 laminectomy and cervical 2-5 dorsal internal fixation and fusion. Postoperatively, the patient's neurological exam remained stable and imaging showed improved spinal alignment and appropriate anterior and posterior instrumentation. Unfortunately, the patient thereafter suffered a decline in performance status and progression of lung metastatic disease. Her oncology team is considering chemotherapy and stereotactic radiosurgery, but her prognosis remains grim. CONCLUSION: AC is a rare and aggressive pathology with a poor prognosis despite multimodal therapy. We present the first case of AC metastatic spread to the spine. We aim to bring this pathology to the attention of our worldwide neurosurgical colleagues and share our surgical approach and multidisciplinary management to assist those who may encounter this pathology in the future.